2012
DOI: 10.1111/j.1751-228x.2011.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Regulation on the Stroop Predicts Reading Achievement in School Age Children

Abstract: In this study we examined high frequency heart rate variability (HF‐HRV, a parasympathetic index) both at rest and during challenge, to assess if variations in cardiovascular activity measured during a Stroop task could be used to predict reading achievement in typically developing children. Reading achievement was examined using the Peabody Individual Achievement Test–Revised. Results showed that greater HF‐HRV suppression during both the Stroop word and Stroop word–color conflict tasks was associated with be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…This interpretation is consistent with polyvagal theory (Porges, ) and studies showing that RSA withdrawal is related to greater sustained attention, engagement during challenge tasks, and on‐task classroom behaviors (Blair & Peters, ; Calkins et al ., ; Calkins & Keane, ; Doussard‐Roosevelt et al ., ; Staton et al ., ; Suess et al ., ). Our results also corroborate previous studies that link a single‐score measure of RSA withdrawal to greater EF skills in low‐risk groups of young children (Becker et al ., ; Marcovitch et al ., ; Skowron et al ., ; Sulik et al ., ; Utendale et al ., ) and higher levels of parent‐rated EF skills (Hastings et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This interpretation is consistent with polyvagal theory (Porges, ) and studies showing that RSA withdrawal is related to greater sustained attention, engagement during challenge tasks, and on‐task classroom behaviors (Blair & Peters, ; Calkins et al ., ; Calkins & Keane, ; Doussard‐Roosevelt et al ., ; Staton et al ., ; Suess et al ., ). Our results also corroborate previous studies that link a single‐score measure of RSA withdrawal to greater EF skills in low‐risk groups of young children (Becker et al ., ; Marcovitch et al ., ; Skowron et al ., ; Sulik et al ., ; Utendale et al ., ) and higher levels of parent‐rated EF skills (Hastings et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, extant studies suggest that higher levels of cool and adult‐reported EF skills may relate to higher initial RSA levels (Chapman et al ., ; Marcovitch et al ., ; Mezzacappa et al ., ; Staton et al ., ; Taylor et al ., ). In contrast, the link between EF skills and RSA reactivity is more tenuous – possibly curvilinear, qualified by sample characteristics or contextual experiences (Becker et al ., ; Marcovitch et al ., ; Skowron et al ., ; Utendale et al ., ). As a result, we examined how EF skills relate to both linear and quadratic RSA change during the challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to HRV-reactivity, to our knowledge no studies have considered race differences in age trends, despite the potential importance of HRV-reactivity as a stress-sensitive biomarker of cardiac autonomic control (Becker et al, 2012; Blair & Peters, 2003; Blascovich & Mendes, 2010; Duschek et al, 2009; El-Sheikh & Erath, 2011; Porges, 2007; Rottenberg et al, 2005). Indeed, because limited evidence supports African American vulnerability in resting HRV, HRV-reactivity may be particularly important in understanding possible racial differences in aspects of ANS functioning that may be linked to disease.…”
Section: Race and Aging Of The Autonomic Nervous Systemmentioning
confidence: 99%
“…Results are inconsistent in two aspects (see Graziano & Derefinko, 2013;Obradović & Finch, 2016Porges, 2007 Greater RSA withdrawal in response to various laboratory challenges has been associated with increased sustained attention, engagement during challenge tasks, on-task behaviors in the classroom, and cognitive functioning, as well as more adaptive emotion regulation strategies (Blair & Peters, 2003;Calkins, Blandon, Williford, & Keane, 2007;Calkins & Keane, 2004;Doussard-Roosevelt, Montgomery, & Porges, 2003;Staton et al, 2009;Suess et al, 1994). Similarly, Becker and colleagues reported that better performance on an EF task was associated with greater RSA withdrawal among elementary school students (Becker et al, 2012). However, Utendale and colleagues found that greater EF skills were associated with lower RSA withdrawal among 5-and 6-year-olds, a relationship further moderated by children's externalizing problems (Utendale et al, 2014).…”
Section: Are the Largest Phasic (Reactive) Changes Observed At Intermmentioning
confidence: 99%